Urgensi Penyidik Pegawai Negeri Sipil dalam Penegakan Hukum Tindak Pidana di Bidang Lingkungan Hidup - Kresna Adicandra; Teguh Suratman (MLJ Merdeka Law Journal, 2020)
This study analyzes the urgency of civil servant investigators in law enforcement in environmental matters. The method used in this research is normative legal research using the Legislation approach and conceptual approach. The legal material used includes primary, secondary and tertiary legal materials, with the analysis of the chosen legal material being descriptive analysis. The results showed that the urgency of civil servant investigators as criminal investigators in the environmental field in the criminal justice system is an investigation based on special abilities from the results of technical skills training held by PPNS for criminal acts in the environmental field in relation to criminal acts. The existence of PPNS in the environmental field was presented because investigators (Polri) faced certain obstacles in investigating criminal acts in the environmental field.DOI: https://doi.org/10.26905/mlj.v1i1.4289.